Transcriptomic Analysis of the Innate Antiviral Immune Response in Porcine Intestinal Epithelial Cells: Influence of Immunobiotic Lactobacilli - Albarracin, Leonardo; Kobayashi, Hisakazu; Iida, Hikaru; Sato, Nana; Nochi, Tomonori; Aso, Hisashi; Salva, Susana; Alvarez, Susana; Kitazawa, Haruki; Villena, Julio (Frontiers in Immunology, 2017)
Lactobacillus rhamnosus CRL1505 and Lactobacillus plantarum CRL1506 are immunobiotic strains able to increase protection against viral intestinal infections as demonstrated in animal models and humans. In order to gain insight into the host-immunobiotic interaction, the transcriptomic response of porcine intestinal epithelial (PIE) cells to the challenge with viral molecular associated pattern poly(I:C), and the changes in the transcriptomic profile induced by the immunobiotics strains CRL1505 and CRL1506 was investigated in this work. By using microarray technology and RT-PCR we obtained a global overview of the immune genes involved in the innate antiviral immune response in PIE cells. Stimulation of PIE cells with poly(I:C) significantly increased the expression of IFN-α and IFN-β, several interferon-stimulated genes, cytokines, chemokines, adhesion molecules, and genes involved in prostaglandin biosynthesis. It was also determined that lactobacilli differently modulated immune gene expression in poly(I:C)-challenged PIE cells. Most notable changes were found in antiviral factors (IFN-α, IFN-β, NPLR3, OAS1, OASL, MX2, RNASEL) and cytokines/chemokines (IL-1β, IL-6, CCL4, CCL5, CXCL10) that were significantly increased in lactobacilli-treated PIE cells. Immunobiotics reduced the expression of IL-15 and RAE1 genes that mediate poly(I:C) inflammatory damage. In addition, lactobacilli treatments increased the expression PLA2G4A, PTGES and PTGS2 that are involved in prostaglandin E2 biosynthesis. L. rhamnosus CRL1505 and L. plantarum CRL1506 showed quantitative and qualitative differences in their capacities to modulate the innate antiviral immune response in PIE cells, that would explain the the higher capacity of the CRL1505 strain when compared to CRL1506 to protect against viral infection and inflammatory damage in vivo. These results provided valuable information for the deeper understanding of the host-immunobiotic interaction and their effect on antiviral immunity. The comprehensive transcriptomic analyses successfully identified a group of genes (IFNβ, RIG1, RNASEL, MX2, A20, IL27, CXCL5, CCL4, PTGES and PTGER4), which can be used as prospective biomarkers for the screening of new antiviral immunobiotics in PIE cells and for the development of novel functional food and feeds, which may help to prevent viral infections.